Способы улучшения инфракрасного изображения с помощью совмещения телевизионного и инфракрасного изображения - Гончаров, А. С.; Бондаренко, И. Н. (ХНУРЕ, 2019)
In recent years, there has been an increasing interest in developing objective image quality assessment methods that can automatically predict human behaviors in evaluating image quality. Such perceptual IQA measures have broad applications in the evaluation, control, design and optimization of image acquisition, communication, processing and display systems. Here is a comparison of methods for processing and improving the infrared image.
Keywords: Способы улучшения инфракрасного изображения; инфракрасное изображение; телевизионное изображение; совмещение изображений